Analysis of Factors Affecting Adolescent Mental Health Based on Social Cognitive Theory (SCT) - Yunita, Astri; Maula, Liya Ni’matul; Suprapti, Dwi (Poltekkes Kemenkes Palu, 2025)
Background: Adolescent mental health is an emerging global concern, with nearly half of adolescents—about 46%—at risk of mental disorders, and 21% experiencing severe impairment. Based on Social Cognitive Theory, which highlights reciprocal interactions among environmental, behavioral, and cognitive factors, this study aimed to analyze factors influencing adolescent mental health. Method: This quantitative cross-sectional study aimed to analyze factors influencing adolescent mental health. The research involved 112 adolescents from Gadungan Village, selected through non-probability (accidental) sampling, and was conducted in August 2025. Independent variables included environmental, behavioral, and cognitive factors, while adolescent mental health served as the dependent variable. Results: The bivariate results indicate a significant relationship between environmental factors (p < 0.001), behavioral factors (p < 0.001), and cognitive factors (p < 0.001) and adolescent mental health. Based on the results of multiple linear regression, it was found that the most dominant factor affecting adolescent mental health was behavioral factors, with a value of p < 0.001. The adjusted R-square value was 50.5%, which means that the variables in this study were able to show the factors that influence the mental health of adolescents. Conclusion: Excessive social media and technology use negatively affect well-being through social comparison, sleep disruption, and reduced face-to-face interaction. Adaptive coping and a healthy lifestyle mitigate distress and promote emotional and physical health. However, self-efficacy alone is insufficient without supportive environmental factors, reinforcing the SCT framework’s emphasis on the interplay of personal, behavioral, and environmental determinants.